Harnessing the power of natural alkaloids: the emergent role in epilepsy therapy - Li, Siyu; Lin, Xinyu; Duan, Lijuan (Frontiers in Pharmacology, 2024)
The quest for effective epilepsy treatments has spotlighted natural alkaloids due to their broad neuropharmacological effects. This review provides a comprehensive analysis of the antiseizure properties of various natural compounds, with an emphasis on their mechanisms of action and potential therapeutic benefits. Our findings reveal that bioactive substances such as indole, quinoline, terpenoid, and pyridine alkaloids confer medicinal benefits by modulating synaptic interactions, restoring neuronal balance, and mitigating neuroinflammation-key factors in managing epileptic seizures. Notably, these compounds enhance GABAergic neurotransmission, diminish excitatory glutamatergic activities, particularly at NMDA receptors, and suppress proinflammatory pathways. A significant focus is placed on the strategic use of nanoparticle delivery systems to improve the solubility, stability, and bioavailability of these alkaloids, which helps overcome the challenges associated with crossing the blood-brain barrier (BBB). The review concludes with a prospective outlook on integrating these bioactive substances into epilepsy treatment regimes, advocating for extensive research to confirm their efficacy and safety. Advancing the bioavailability of alkaloids and rigorously assessing their toxicological profiles are essential to fully leverage the therapeutic potential of these compounds in clinical settings.